Analisis Operation Research dengan Metode Transportasi, MODI dan Stepping Stone pada Proses Distribusi untuk Meminimasi Biaya Pengiriman di CV. Partoba Jakarta - Angel, Beauty; Iskandar, Hendi; Wibowo, Priyo Ari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The distribution of goods or services is crucial for both governmental institutions and specific companies. Method (VAM), Least Cost method (LC), and North West Corner (NWC), and achieves an optimal solution with the MODI method. Through analysis and calculations, it concludes that initially, Vogel's Approximation Method (VAM) is more optimal compared to the Least Cost and North West Corner methods. This conclusion is supported by finding the optimal MODI and Stepping Stone values. Further testing using POM - QM software confirms that employing this software optimizes distribution costs and allocates fresh fish distribution effectively for CV. Partoba. After calculations, the optimal distribution cost is determined to be Rp35,778,060, resulting in a cost reduction of Rp4,414,035, representing savings of 10.98% for the company.